(untitled) - Robert J Hunter (Oxford, New York, 1993)
Colloidal systems also important in the paper, paint, and ink industries, either in the final products or at crucial stages in their manufacture. This book provides an introduction to the area of science which seeks to understand those processes which govern the behaviour of these systems
Keywords: colloids